Characterization of starch morphology, composition, physicochemical properties and gene expressions in oat - Ke ZHENG; Qian-tao JIANG; Long WEI; Xiao-wei ZHANG; Jian MA; Guo-yue CHEN; Yu-ming WEI; Mitchell Fetch Jennifer; Zhen-xiang LU; You-liang ZHENG (Journal of Integrative Agriculture, 2015)
Starch is the major carbohydrate in oat (Avena sativa L.) and starch formation requires the coordinated actions of several synthesis enzymes. In this study, the granule morphology, composition and physicochemical properties of oat starch, as well as the expressions of starch synthesis genes were investigated during oat endosperm development. Under the scanning electron microscopy (SEM), we observed that the unique compound granules were developed in oat endosperms at 10 days post anthesis (DPA) and then fragmented into irregular or polygonal simple granules from 12 DPA until seed maturity. The amylose content, branch chain length of degree of polymerization (DP=13–24), gelatinization temperature and percentage of retrogradation were gradually increased during the endosperm development; whereas the distribution of short chains (DP=6–12) were gradually decreased. The relative expressions of 4 classes of 13 starch synthesis genes characterized in this study indicated that three expression pattern groups were significantly different among gene classes as well as among varied isoforms, in which the first group of starch synthesis genes may play a key role on the initiation of starch synthesis in oat endosperms.